Identifying factors related to the sense of coherence of adult asthmatics in Dumaguete City - Guino-o, Theresa A. (Silliman Journal, 2007)
This study examines the relationship between the Sense of Coherence (SOC) and selected variables in 159 asthmatics, aged 20-40 years old. A two-part self-administered questionnaire was used to collect both the demographic data and the SOC levels of respondents using the "Orientation of Life Questionnaire" (OLQ). The data revealed that a majority of adult asthmatics have a high sense of coherence. No significant relationship was seen between SOC and age, gender, marital status, and educational attainment. Moreover, no significant relationship was observed between SOC and the nature and perceived helpfulness of societal support, level of major stressful events, and the self-reported health status levels of respondents. However, a significant relationship was observed between SOC levels of adult asthmatics and their perceived societal cohesion and structure as well as their levels of health maintaining behaviors. These findings strengthen the validity of the concepts of salutogenesis and the knowledge that SOC influences the maintenance of a person's health. Thereby, SOC may be tapped as a health management resource for people with asthma or other health related conditions.